FUNGSI DAN PEMERIKSAAN LIMFOSIT γδT (Functions and Examination of γδT lymphocytes) - Yulia Nadar Indrasari; Jusak Nugraha (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
T lymphocytes most have TCR α and β chains. However, TCR formed from γ and δ chains determine a new subset of T lymphocytes. γδTCR specific to different types of ligands, including bacterial phosphoantigen, nonclassical MHC-I molecules and unprocessed protein. γδT lymphocytes have several innate cell-like features that allow their early activation following the recognition of conserved stress-inducedligands. γδ T lymphocytes able to rapidly produce cytokines that regulate pathogen clearance, inflammation and tissue homeostasisin response to tissue stress. They are capable of generating more unique antigen receptors than γδ T lymphocytes and B lymphocytescombined, yet their repertoire of antigen receptors is dominated by specific subsets that recognize a limited number of antigens. A varietyof sometimes conflicting effectors functions have been ascribed to them, yet their biological functions remain unclear. Innate featuresof γδ T lymphocytes underlie their non-redundant role in several physiopathological contexts and are therefore being exploited in thedesign of new immunotherapeutic approaches. The purpose of writing is giving an overview in mainly functions of γδ T lymphocytes inthe immune system and laboratory tests that expand knowledge about the introduction of γδ T lymphocytes.